SOMATOMETRY OF SWAMP BUFFALO IN JEMBRANA DISTRICT BALI - Manurung, Debora Selfia Br; Wandia, I Nengah; Suatha, I Ketut (Buletin Veteriner Udayana; Vol. 9 No. 1 Pebruari 2017, 2017)
This study aimed to reveal somatometric variation in the population of swamp buffalo ( Bubalus Bubalis ) in Ijo Gading West Team and Ijo Gading East Team in Jembrana. This study involved 68 swamp buffalo (37 in Regu Ijo Gading Barat and 26 in Regu Ijo Gading Timur). The variables of this Somatometric are the height of its shoulder, its hip, the round of its chest, its long, and its neck. The final result of this test is there is no difference somatometric on both popuoations. Result of the main component analysis is shows that the character of its shapes and size from both populations are the same. The characteristic factors of its size are the round of its chest and its long. In other wise the characteristic factors of its shapes are the height of its shoulder and its hip. The round of its chest give a significant shapes factor but it is negative. In fact there is not too much different betwen both population somatometricaly.
Keywords: kerbau lumpur, morfometri, somatometri